The chemistry of acacia gums - Alexander Jacob Charlson (Department of Chemistry, 2024)
Gummy material is often exuded in response to injury by trees belonging to the Rosaceae and Leguminosae families. Acacia trees belong to the Leguminosae family, and the exudate from a variety of acacia species is known as "gum arabic" or "gum acacia". Gum arabic is collected for industrial use from acacia trees grown in hot, dry climates. The most esteemed variety is obtained from kordofan, although senegal and rnogador gums are or excellent quality.